PENGARUH PELATIHAN, BUDAYA ORGANISASIONAL TERHADAP KINERJA GURU PAUD DENGAN MEDIASI MOTIVASI KERJA (Studi pada UPT Dinpendik Kec.Rembang Kabupaten Rembang - Hermawan Andi Kusbianto, 1142020132 (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of this study was to examine the effect of training, organizationalÂ  culture on the performance of early childhood teachers and test work motivation may mediate training and organizational culture on the performance of early childhood teachers. The population of this research is early childhood teachers in UPT Dinpendik Kec.Rembang Rembang much as 291 people. The research instrument used in this study is the validity and reliability, the analysis tool used is multiple regression, hypothesis testing using t test and mediation. Questionnaire as the primary data collection tool, the Likert scale of measurement used are 5 alternative answer to the secondary data obtained by observation, documentation and interviews.